Flood proofing in urban areas. - Bignami, Daniele Fabrizio; Rosso, Renzo; Sanfilippo, Umberto (Springer, 2019)
The book shows that temporary facilities under appropriate planning procedures based on a quantitive approach can be used to approach flood risk mitigation. The book provides a rationale for choosing the proper flood proofing option from the multifaceted standard and non-standard facilities depending on the specific urban and suburban patterns. The approach is developed at different spatial scale, all-encompassing the district, city block and building scales.
Keywords: Stadtplanung; Überschwemmung; Hochwasserschutz; Resilienz; Gebäudeschutz; Planungsprozess; Folgenabschätzung; Schutzmaßnahme; Modell; Temporäre Architektur; Technische Anlage; Deich; Barriere